Preferential oxidation (prox) of carbon monoxide (co) in hydrogen rich stream over copper supported on cobalt based catalysts - Tsoke, Choene Clement (My University, 2024)
The use of hydrogen (H2) fuel as an alternative source of energy for transportation and residential applications has recently increased. Polymer electrolyte membrane fuel cells (PEMFCs) use hydrogen produced from steam reformer and water gas shift as source of energy. The presence of trace amount (~0.5 – 2 vol.%) of carbon monoxide (CO) lower the efficiency of the fuel cells which prefers CO less than 10 ppm. Preferential oxidation of carbon monoxide (CO(PROX)) is a preferred method for the reduction of CO and a suitable catalyst with less selectivity to hydrogen species is required for this process. Transition metal oxide catalysts, such as CuOx, Co3O4, CeO2, ZrO2, MnOx etc are used for CO(PrOx) reaction. However, it still a challenge to prepared highly stable CO(PrOx) catalysts that can oxidize CO with minimal selectivity to H2, especially in the presence of moisture and CO2 in the feed stream. The study reports various catalysts based on CuOx and CeO2 supported on Co3O4 catalysts, prepared by facile hydrothermal and reflux assisted precipitation and/or co-precipitation methods. The catalysts were prepared in the presence of surfactant/polymer (CTAB/PVP) mixture and used for CO(PrOx) reaction. The structural features of the synthesised catalysts were investigated by FTIR, XRD, SEM, BET, TEM, H2-TPR and TGA-DTA analysis. The presence of Co3+ and Co2+ stretching vibrations in all the prepared samples was revealed by the FTIR analysis and arose from Co3O4 phase, as confirmed by XRD spectroscopy. CO(PrOx) data showed that the introduction of CeO2 to Co3O4(Hyd) and Co3O4(Ref) catalysts by either hydrothermal or reflux route slightly increased the catalytic activity with temperature in dry CO(PrOx). The CuOx dopant on the other hand drastically increased the catalytic performance of Co3O4 catalyst as compared to CeO2, with 5 wt.% CuOx being an optimum load in both methods. However, doping CuOx by reflux to obtain 5 wt.% CuOx /Co3O4(Ref) catalyst, had enormous positive influence on CO(PrOx) activity, archiving almost 94% CO Conversion at 40 oC, while 5 wt.% CuOx /Co3O4(Hyd) achieved 74% CO conversion. The 5 wt.% CuOx /Co3O4(Ref) catalyst consists of CuOx species substituted within the Co3O4 framework, which increased the metal-support interactions and featured a smaller crystallite size, high surface area (SBET = 64.9 m2/g) and large pore size distribution. While the 5 wt.% CuOx /Co3O4(Hyd) counter catalyst showed just 57.6 m2/g SBET and had relatively small pore sizes. The CO oxidation as a function of temperature in moisture saturated feed gas showed negative effects over the as prepared catalyst’s sample. When tested for stability in moisture environment, the 5 wt.% CuOx /Co3O4(Ref) catalyst demonstrated relatively good stability over time on stream, as compared to the 5 wt.% CuOx/Co3O4(Hyd) counterpart. Co-feeding 15 vol.% CO2 into the reactor stream demonstrated a negative influence on the catalytic stability over 5 wt.% CuOx /Co3O4(Hyd) catalyst, where’s 5 wt.% CuOx /Co3O4(Ref) catalyst still showed a good CO conversion. Introduction of CeO2 on the optimized bimetallic 5 wt.% CuOx/Co3O4 catalysts by similar preparation procedures to obtain a ternary catalyst resulted in a low CO(PrOx) performance, due to lowered surface area and morphology alterations as probed by the BET and SEM analysis. The ternary samples had a highly coarsened surface, with a high degree of irregularity. Under reflux method, the pore volume was also reduced dramatically upon CeO2 addition due to blockage by agglomerated nanoparticle (TEM evident). As a result, the stability in CO2 environment over 5 wt.% CuOx/Co3O4(Ref) catalyst was tremendously decreased. However, the % CO2 selectivity in these hash conditions (CO2 and H2O) over 5 wt.% CuOx /Co3O4(Ref) and 5 wt.% CuOx /Co3O4(Hyd) catalyst was improved upon ceria addition, ascertaining the role of CeO2 in moisture and CO2 resisting catalyst development.
Thesis (M.Sc. (Chemistry)) -- University of Limpopo, 2024
Keywords: Energy; Transportation; Hydrogen; Water gas; Oxidation; Carbon monoxide; Hydrogen as fuel; Oxidation; Water-gas